KANDUNGAN KADMIUM DI DALAM WORTEL, BAWANG PREI DAN BUNCIS YANG DITANAM PADA TANAH BERBAHAN INDUK KAPUR DAN VOLKANIK DENGAN DOSIS PUPUK P YANG BERBEDA - Charly Mutiara (AGRICA, 2014)
This study aims at investigating the content of cadmium on carrots, leeks, and string bean grown on limestone and volcanic soil with different dose of P Fertilizer and comparing the contents with cadmium content standardized by FAO/WHO. This pot test employed random block design and was a factorial test with three factors, namely factor of plant species, soil type, and fertilizer dose with three repeated tests. The levels of each factor are plants species consisting of Carrot (C1), leek (C2), and string bean (C3); soil type comprises of Andosol Nduaria (S1), MollisolFatumnasi (S2), VertisolOesao (S3) and MollisolBaumata (S4) and the fertilization consists of three levels of P fertilizer, namely 100 kg SP-36 per ha (F3), 50 kg SP-36 per ha (F2) and without P fertilizer (F1). The result of this study shows that the prediction model of cadmium content on the carrot, leek, and string bean based on cadmium, pH, electricity power, and land organic C content cannot be revealed in this study since the cadmium content cannot be detected by AAS. Moreover, the cadmium content on the carrot, leek, and string bean planted on four soil types and given different doses of P Fertilizer are under the standard set up by FAO/WHO (<0,05-01 mg kg-1).